TINDAK PIDANA PENGEDARAN DAN PENYALAHGUNAAN OBAT FARMASI TANPA IZIN EDAR MENURUT UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Andin Rusmini (Al-Adl : Jurnal Hukum, 2017)
The rise of drug trafficking without marketing authorizationin the societyis very distressedus as members of society. It shows that the people’s awareness of the law is still very low that tends to commit criminal offenses including distributing pharmaceutical preparations without a marketing authorization. This study was conducted to determine how the rule of law against the crime of distributing pharmaceutical preparations without a marketing authorization and the efforts made to overcome them. This research uses normative juridical method using secondary data through library is conducting research on various sources of literature books, laws and regulations relating to the crime of distributing pharmaceutical preparations without a marketing authorization. The result of the research conducted can be concluded that the crime of distributing pharmaceutical preparations without a marketing authorization as stipulated in act No. 36 Year 2009 on Health serves as optimizing the criminal act as a tool in crime prevention efforts. Application of the Act is expected to ensnare the perpetrators distribute pharmaceutical preparations without a marketing authorization. As well as the efforts to be made in the handling of this criminal act is done with penal and non-penal policies.Keywords: Crime, Authorization, Drug.